Potent affinity material for tracing acetone and related analytes based on molecular recognition by halogen bonds12. Issue 11 (23rd December 2014) - Linke, Alexander; Jungbauer, Stefan H.; Huber, Stefan M.; Waldvogel, Siegfried R.
Abstract : A helping third hand converts halogen bonds into a superior recognition tool. Abstract : Affinity materials based on halogen bonds turned out to be a powerful tool for the molecular recognition of acetone or related carbonyl compounds in the presence of ubiquitous protic molecules. The superior selectivity and sensitivity were found by the gravimetric detection of volatile organic compounds by quartz crystal microbalances.